Genes HLA de classe II (DRB1 e DQB1) como fatores de risco para a toxoplasmose ocular - Camargo, Ana Vitória da Silveira (2016)
Toxoplasmosis, a disease resulting from Toxoplasma gondii infection, is clinically manifested through ocular, cerebral and congenital ways. This pararsito Apicomplexa is capable of infecting cells of all nucleated tissues and may remain in a latent state or cause irreversible cell damage. The HLA class II genes control the adaptive immune response humoral and influence susceptibility and the resistance to infectious and parasitic diseases. The ocular toxoplasmosis, besides being dependent on infection with T. gondii as well as the variability of the infecting strain, is influenced by host genetic factors. Aim: To test the hypothesis that the HLA class II genes (HLA-DRB1 and HLA-DQB1) are associated with ocular toxoplasmosis. Materials and Methods: Samples of 249 patients undergoing ophthalmologic evaluation and positive serology to T. gondii were analyzed. According to the clinical conditions, two distinct groups were composed: one formed by patients with ocular toxoplasmosis (n=123); and another group with patients without the disease ocular form (n=126). The patients with ocular toxoplasmosis were subdivided into two groups, according to the type of ocular manifestation: primary (n=93 samples) or recurrent (n=30). Genotyping of Class II HLA alleles were performed by the polymerase chain reaction technique with specific oligonucleotide sequence (PCR-SSO; One Lambda®). Results: The average ages of the group of patients with ocular toxoplasmosis was less (40.9±19.9) than the average age of patients without ocular toxoplasmosis (57.6±17.2) (p<0.0001).The alleles HLA-DRB1*03 (OR=1,94; IC 95% 1.09-3.45; p=0.031; pc=0.404) and HLA-DQB1*02 (OR=1.52; IC 95% 1.03-2.24; p=0.039; pc=0.197) showed a more allelic frequency in patients without ocular toxoplasmosis when compared to the group with ocular toxoplasmosis. The HLA-DRB1*14 alelle was more frequent in the subgroup of the recurrent manifestation, when compared to the group without ocular toxoplasmosis (OR=0.32; IC 95% 0.12-0.83; p=0.032; pc=0.417) and to the primary manifestation subgroup (OR=0.25; IC95% 0.08-0.73; p=0.017; pc=0.223). The HLA-DRB1*03_DQB1*02 haplotype was not associated with the lower risk of ocular toxoplasmosis (OR=1.86; IC 95%: 1.03-3.36; p=0.052). Conclusions: The obtained results suggest that the Class II HLA genes (DRB1 and DQB1) are not associated with the ocular toxoplasmosis development; and that none HLA DRB1_DQB1 haplotype influences the ocular toxoplasmosis development in the study population.